Visual Histories of Occupation A Transcultural Dialogue - Taylor, Jeremy E. (Bloomsbury Academic, 2021)
This book is open access and available on www.bloomsburycollections.com. It is funded by the European Research Council. Asking what does foreign occupation look like and how does occupation shape visual expression and cultures, this edited collection explores how the occupied and occupiers have responded to their circumstances through visual culture. Contributors study specific cases of foreign occupation from around the world and across the 20th century, discussing the similarities, links and points of contact which bring disparate examples of occupation into dialogue with one another. The intention is to illustrate how an emphasis on 'the visual' can help inform our understanding of occupation more broadly. Comprised of 12 core chapters and structured around 4 methodological and conceptual themes, this book adopts a consciously transcultural approach through which contributors examine the influence of specific cases, memories and legacies of occupation. Spanning Europe, Asia, the Middle East and elsewhere, the chapters also engage in a wider dialogue to reveal commonalities and points of comparison across political and temporal boundaries.